PELAKSANAAN SISTEM KOORDINASI PENGAWASAN ORANG ASING KOTA SABANG DILIHAT DARI ASPEK HUKUM KEIMIGRASIAN SEBAGAIMANA DIATUR DALAM UNDANG-UNDANG NO. 6 TAHUN 2011 TENTANG KEIMIGRASIAN - FAHROZI FAHROZI (USU LAW JOURNAL, 2013)
The heterogeneous geographical condition of Indonesian territory with the clusters of islands stretching from Sabang to marauke automatically becomes the factor complicating the process of monitoring the existence of foreigners doing activities in the territory of Indonesia in general and in the city of Sabang in particular. Therefore, intensive inter agency coordination is needed in the process of immigration monitoring and enforcement. The problems discussed in this study were how foreigner focused inter agency monitoring coordination system was regulated, how foreigner focused inter agency monitoring coordination was implemented, and what kind of enforcement effort can be done on the violotion of immigration permit reviewed from law no.6/2011 on immigration. According to law no.6/2011, monitoring the foreigners was implemented by the Sabang immigration office through the mechanishm coordinating with the local police, local government, local manpower service, related agencies and local community. Tthe coordination of foreigner monitoring in the Sabang area was done through a joint monitoring, exchanging information about the existence and activities of the foreigners in Sabang area up to the process of legal action either administratively or projustisia. The legal action taken for immigration violations was determined through a deep analysis by the related officials by considering the effectiveness of the handling process of the cases occurred in one region of the republic of Indonesia including the city of Sabang. Key words :  Implementation, Coordinating system, Monitoring coordination, Law no.6/2011